Optimization of the synthesis of SBA-3 mesoporous materials by experimental design - Ponte, María Virginia (2016)
SBA-3 mesoporous materials are characterized by hexagonal regular arrangements of channels with diameters >2 nm, high specific surface areas and high specific pore volumes. In the work reported herein, experimental design-response surface methodology (RSM) is used to model and optimize the synthesis conditions for SBA-3 mesoporous materials. In this study, we evaluate the influences of surfactant/silica source molar ratios, aging times, temperature and pH on the synthesis of SBA-3 mesoporous materials by analyzing the XRD intensities pertaining to the [100] signal. Response surfaces were obtained using theBoxeBehnken design, and the combination of reaction parameters was optimized. By applying statistical methodology, higher levels of the objective function (XRD intensities pertaining to the [100] signal) were obtained using cetyltrimethylammonium bromide (CTAB)/tetraethyl orthosilicate (TEOS) molar ratios of 0.07 and 0.16, HCl/TEOS molar ratios of 8 and 11, reaction temperatures of 35 and 45 C and aging times of 12e24 h. The mesoporous SBA-3 samples obtained were characterized using small-angle X-ray powder diffraction (XRD), BET, FTIR and 29Si NMR-MAS, scanning electron microscopy (SEM) andtransmission electron microscopy (TEM).